Training Of Disaster Response Cadres (Tagana) Reproductive Health Of Penyengat Olak Village Muaro Jambi Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
BNPB recorded more than 1,200 disasters occurred from the beginning of the year to early May 2020. Disaster events were still dominated by hydrometeorological disasters, such as floods, landslides and tornadoes. BNPB data states that 172 people died as a result of the disaster. BNPB identified that more than 99% of disaster events were hydrometeorological disasters. The most dominant disasters are floods with 457 occurrences, 359 tornadoes, 275 landslides and tidal waves or abrasion 2. In addition, another category of hydrometeorological disasters with a high number is forest and land fires (karhutla), 119 times. The total number of disasters is 1,221. In addition to these disasters, BNPB also recorded other disasters such as 3 volcanic eruptions and 5 earthquakes.